KARAKTERISTIK PROKSIMAT DAN KANDUNGAN SENYAWA KIMIA DAGING PUTIH DAN DAGING MERAH IKAN TONGKOL (Euthynnus affinis) - H Hafiludin (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2011)
Indonesia has a marine biological resources are very large with the content of various types of creatures living in it. The biological richness of which are fish that have a benefit in the field of food and health. Tunafish (Euthynnus affinis) is a species that is very interesting to study both in terms of nutritional composition and in terms of its economy. The purpose of this study was to determine the nutrient content and chemical compounds contained in red meat and white meat tuna. Research methodology includes observation of morphology, proximate analysis and phytochemical analysis of tuna. The highest yield was found in meat that 50%. Proximate protein content of the highest in the white meat that was 68.36%, the highest fat in red meat was 5.6%, the highest in red meat ash 3.29%, and the highest water on the white meat that was 12.16%. In the white meat and red meat tuna contained alkaloid, steroid, and carbohydrate compounds (molisch). Keywords: proximate, chemical compounds, tuna (Euthynnus affinis)